Answers

The Brainliest Answer!
2016-02-11T23:51:39+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Assuming root 'a'
Therefore, second root = 6a
Both satisfy equation kx^2-14x+8 = 0

1. Substituting root 'a' into equation:
=> ka^2-14a+8 = 0 ...(1)
=> 9ka^2-126a+72 = 0 (Multiplying equation with 9) ...(2)

2. Substituting root 6a into the equation:
=> 36ka^2-84a+8 = 0
=> 9ka^2-21a+2 = 0 (Dividing equation by 4) ...(3)
Subtracting equations (3) from (2), we get
=> -105a+70 = 0
=> a = 70/105 = 2/3

Substituting root 'a' in equation (1)
=> 4k/9-28/3+8 = 0
=> (4k-84+72)/9 = 0
=> 4k-12 = 0
=> 4k = 12
=> k = 3

Alternate Method, which is too much effort to type out:
3 4 3